1987
DOI: 10.2208/jscej.1987.386_43
|View full text |Cite
|
Sign up to set email alerts
|

Natural Frequency of a Fill Dam by Means of Two Dimensional Truncated Wedge Taking Shear and Bending Moment Effects Into Account

Abstract: The discussion, in this paper, is confined to the natural vibration of the fill dam which can be described by the truncated wedge of inhomogeneous rigidity: G=Gm(z/hY where G: modulus of rigidity, z: distance from the top of dam, h: dam height, n: rigidity index, and with rectangular canyon shape. Equilibrium of the bending moment and the shearing force in the vertical direction, together with the shearing force and twisting moment in the transverse direction, leads to the fundamental dynamic equations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Their results indicated that inclination in the wet surface of the dam reduces hydrodynamic pressures. Natural frequencies of a fill dam with a wedge section was calculated by Kishi et al (1987) considering both shear and bending effects. They implemented finite difference in their calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that inclination in the wet surface of the dam reduces hydrodynamic pressures. Natural frequencies of a fill dam with a wedge section was calculated by Kishi et al (1987) considering both shear and bending effects. They implemented finite difference in their calculations.…”
Section: Introductionmentioning
confidence: 99%